IMPLEMENTASI KEBIJAKAN PUBLIK PERATURAN DAERAH PROVINSI RIAU NOMOR 6 TAHUN 2012 - Firman Hidayat; Meyzi Heriyanto; Firdaus Firdaus (Universitas Riau, 2018)
Implementation of Public Policy of Riau Province Regional Regulation Number 6of 2012. This study aims to evaluate the effectiveness of the implementation of Riau ProvincialRegulation No. 6 of 2012 concerning Corporate Social Responsibility in Riau Province. Thisresearch is descriptive and explorative qualitative research. The research informants were theDumai City Government bureaucracy, the Industry and Trade Office, the company and thecommunity in Dumai, Buluh Kasab and Datuk Laksamana. Data collection techniques areinterviews, observation and documentation. Data analysis uses interactive models through theprocess of data reduction, data display and conclusion drawing or data verification. From theresults of the study it was found that the implementation of the Riau provincial government policyon the Corporate Social Responsibility and the Environment was not effective.